2017
DOI: 10.3758/s13414-017-1279-8
|View full text |Cite
|
Sign up to set email alerts
|

Object detection in natural scenes: Independent effects of spatial and category-based attention

Abstract: Humans are remarkably efficient in detecting highly familiar object categories in natural scenes, with evidence suggesting that such object detection can be performed in the (near) absence of attention. Here we systematically explored the influences of both spatial attention and category-based attention on the accuracy of object detection in natural scenes. Manipulating both types of attention additionally allowed for addressing how these factors interact: whether the requirement for spatial attention depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…The beneficial influence of content-based attention appears to reflect a general mechanism that can operate at different levels of abstractness of stimulus content, from simple stimulus features to basic-level object categories and even superordinate categories. 30,31 These findings demonstrate that content-based attention can influence performance in even the most basic perceptual tasks, similar to spatial attention. This does not necessarily imply that content-based and spatial attention rely on identical cognitive and neural mechanisms.…”
Section: The Influence Of Spatial and Content-based Attention On Behamentioning
confidence: 89%
See 2 more Smart Citations
“…The beneficial influence of content-based attention appears to reflect a general mechanism that can operate at different levels of abstractness of stimulus content, from simple stimulus features to basic-level object categories and even superordinate categories. 30,31 These findings demonstrate that content-based attention can influence performance in even the most basic perceptual tasks, similar to spatial attention. This does not necessarily imply that content-based and spatial attention rely on identical cognitive and neural mechanisms.…”
Section: The Influence Of Spatial and Content-based Attention On Behamentioning
confidence: 89%
“…For example, Stein and Peelen provided participants with prior information about the orientation of an upcoming grating through a word cue (e.g., “horizontal”) and found that accuracy in detecting and localizing briefly presented, low‐contrast targets was better when the orientation of the target matched the word cue, even though orientation was irrelevant to the detection task. The beneficial influence of content‐based attention appears to reflect a general mechanism that can operate at different levels of abstractness of stimulus content, from simple stimulus features to basic‐level object categories and even superordinate categories …”
Section: The Influence Of Spatial and Content‐based Attention On Behamentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective investigations are also required to examine more precisely how our findings generalise over different categories of stimuli or stimulus feature differentiation. It has been shown that these aspects can interact with attention and metacognition (Stein & Peelen, 2017;Matthews et al, 2018). In addition, the precise influence of evidence-reliability remains to be elucidated in more extensive work as it has also been shown to affect confidence judgments and metacognition (Boldt, De Gardelle & Yeung, 2017;Bang & Fleming, 2018;Denison & al., 2018).…”
Section: Limitations and Further Questionsmentioning
confidence: 99%
“…Behavioral studies have shown that participants may not be able to localize object categories in natural scenes that have nonetheless been detected (Evans and Treisman, 2005). Others have argued that the detection of familiar object categories may not even require spatial attention at all (Li et al, 2002; see also Stein and Peelen, 2017). These findings suggest that spatially-global category-based attention may be sufficient for detecting target-diagnostic features.…”
Section: Discussionmentioning
confidence: 99%